Protection of Post-Divorce Rights According to Islamic Family Law - Ni'matul Mudawamah (Civiliza Publishing, 2026)
Divorce is a social phenomenon that cannot be avoided and has a direct impact on the survival and welfare of children. In the context of Islamic family law, the protection of children's rights is a very important aspect to ensure that children do not become victims of the breakdown of parental relationships. This study aims to analyze the concept of protection of children's rights after divorce, examine its implementation in society, and formulate efforts to improve this protection based on the perspective of Islamic family law. The method used is normative legal research with a qualitative approach based on literature studies, using data sources in the form of the Qur'an, hadith, jurisprudence, laws and regulations, and relevant scientific journals. The data collection technique is carried out through documentation and analyzed using descriptive-analytical methods. The results of the study show that Islamic family law has comprehensively regulated the rights of children after divorce, including the right to maintenance, parenting (hadhanah), education, affection, and protection of children's identity and future. However, implementation in the community still faces various obstacles, especially in the fulfillment of maintenance and parenting that has not been running optimally due to economic factors and low parental awareness. The conclusion of this study confirms that the protection of children's rights in Islamic family law has a strong normative basis, but requires strengthening in the implementation aspect through increasing awareness, law enforcement, and social roles to ensure the fulfillment of children's rights in a sustainable manner.